Modeling and experimental validation of multi-mode four-switch DC-DC converter - Choy, Wei Jun (Nanyang Technological University, 2021)
Renewable storage has been increasingly important over the years, in that it helps to maintain the supply and demand to ensure reliability, resilience, and flexibility to use electricity. The efficiency of the energy system has also been dependent on the types of converters used. As an efficient system, it is very important to achieve high efficiency throughout the power conversion process. Not only that, but it also saved operational costs in powering the power systems.